Examining the impact of servant leadership on turnover intention via organizational affective commitment as mediation: Empirical study - Muzakki Muzakki; Asep Herryanto (Universitas Sains dan Teknologi Komputer, 2023)
This study's objective is to examine the influence of servant leadership on turnover intention and the impact of organizational affective commitment as a mediator between these two relationship constructs. This investigation employs a quantitative methodology by surveying restaurant employees in Surabaya using questionnaires. Utilizing Structural Equation Modeling Partial Least Square (SEM PLS), the collected survey data were analyzed. 78 restaurant employees participated in this investigation as respondents. According to the findings of this study, servant leadership and affective organizational commitment have a significant negative effect on turnover intention. In addition, affective organizational commitment can substantially and negatively moderate the relationship between servant leadership and turnover intention. In this research, both theoretical and practical implications are discussed.